To Barcelona - and not Berlin (press cutting)
808-0015-001 dw. june 9, 1936 6 Round About By Sports Editor TO BARCELONA— AND NOT BERLIN Paris Conference Decision: Much Expected From Britain: London's Soccer Thriller: These Racing "Systems": Armaments And Sport To attend the Paris Fair Play Conference over the weekend was just the tonic I needed. Impressions gained were very deep, for here, plain to all, were true sportsmen fired with determination to save sport from Nazi degradation and its misuse through the medium of the Berlin Games. Most pleasing to witness was the wide support which the International Fair Play Committee commands. Five countries were represented in addition to both Workers' Sport Internationals, while stirring messages came from six other lands, including U.S.A., Egypt, Palestine, Yugoslavia. Norway and Denmark. Lack of cash prevented representatives. Subsidised Professionals CONFERENCE was astounded when told of the fact that Nazis had offered to finance Spanish professionals to compete in Berlin, which served as a forcible reminder that during negotiations for a trade agreement, Iceland had been assured of extra orders from Germany if they guaranteed their participation in the Games. People's Olympiad BARCELONA, of course, received prominence during discussions, and to sport fans like myself, it came as delightful surprise to learn first hand from Catalonian sportsmen the wide appeal which the People's Olympiad on July 22 to 26 had made to ordinary athletes throughout the world, yet at the same time recruited sympathy and support from leading world sportsmen and from university students and intellectuals. Much Expected From Britain I EXPERIENCED a feeling of pride when these sportsmen from other lands applauded the British delegates, who gave details of preparations for sending a big delegation of athletes and spectators to Barcelona. It made me realise at once how they wanted and expected magnificent support from this country, still considered the home of sport. Our lads promised not to let them down. For those interested as spectators, take note of following details. Mr. H. Young, c/o Collet's Bookshop, 66, Charing Cross Road, London, W.C., is organising a party in conjunction with the selection committee. Applications for this party should be made to him. Spectators Trip Details TOTAL expense (bare minimum) £10. London-Barcelona—Barcelona- London. Duration, July 19 to 28. Leaving London 10 a.m., Sunday, July 19. Arriving Barcelona 6.30 p.m., Monday. Route: Through Paris. Return London, Tuesday. July 28. Requirements: Very little luggage is advisable. A change of underclothing and spare outfit (also pair of shorts). A light blanket or coat, or good warm Zipp jacket is handy. Expenses comprise fare, £6 10s ; meals en route; and five days' hotel accommodation in Barcelona at 9s. per day, all-in £2 5s. Third class travel throughout Efforts are being made to get cheaper camping or other accommodation, in which case price will be correspondingly reduced. July 23 is the day of the great Catalonian National festival. All participants must sign a declaration to remain with the party when travelling and accept Mr. Young's instructions in this respect. London's Soccer Thriller LONDON has a great opening to its football season on August 29, when West Ham entertain the Spurs. Hammers, no doubt, will make an extra bid for promotion next season. Though they narrowly failed last, I believe they will make a successful challenge when they take the field again. Strangely enough their last match is against Sheffield United, away from home as was the case last season. All football fans will remember the terrific battle which Division II leading clubs had in the promotion race, in which Sheffield and the Hammers were largely involved Will history repeat itself? These Racing "Systems" I'VE had several letters in on racing systems, showing concern as to advisibility of following same. My advice is keep off all so-called systems as safe investments. They are " all my eye and Betty Martin." Just blarney which simple folk follow. Remember what " Cayton " said about systems. He strongly advises have nothing to do with them. He mentioned the amusing " system " based on astrology, where you are told to " count the number of stars one fine night, and the following day back the horse which has the | same number of letters as the stars, after you have divided by the number of letters in the jockey's name." If the horse goes down "blame the stars," he said, " not me." Keep clear of systems if you do concern yourself with a flutter. Armaments And Sport I'VE got a little leaflet in front of me issued by the British Amateur Weightlifting Association. The association points out that it had attempted to substitute a lifting appliance by name, the Berg Bar, with one on modified lines and cheaper, and submitted same to manufacturers. The modified Bar could be made, but the manufacturers notified the association that they could no longer continue to supply the appliance at the same price in view of ever-increasing demands made upon their resources by reason of the rearmament programme. Which goes to show how frantic are the Government's war preparations, and how strong should be working-class sportsmen's protests. Sports-lovers should cry this scandal from the house-tops. 292/808.91/4/15